Accounting Student Perceptions toward Online Flipped Statistics Course and Effective Methods to Promote Engagement, Increase Satisfaction, and Improve Self-Efficacy - Irene Budi Prastiwi; Sukasah Syahdan (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
The COVID-19 pandemic has motivated many educational institutions in the world to adapt their delivery method from conventional (offline) teaching/learning to online methods, and one of the methods is the Flipped Classroom. Nonetheless, the shift from offline classroom instruction to online learning must ensure its long-term quality, which can be effectively delivered to students. Thus, this study investigates the effectiveness of the an online flipped classroom teaching model as perceived by learners, applied due to the COVID-19 pandemic. The sample for this study includes 41 accounting students taking an online statistics course in their 5th and 7th semesters in a private university in Indonesia. The methods are both quantitative—employed through a questionnaire—and qualitative through applied semi-structured interviews as well as for analyzing the collected corpus. Ultimately, the study concludes that, in terms of student engagement, satisfaction, and efficacy, the flipped classroom method is effective. Lastly, the significance of the research shows recommendations for improving the application of the flipped classroom approach in the current context of online learning amidst the prevailing policy in Indonesia and beyond.